Comparison of the Gut Microbiota Between Pulsatilla Decoction and Levofloxacin Hydrochloride Therapy on Escherichia coli Infection - Liu, Xiaoye; He, Shangwen; Li, Qiuyue; Mu, Xiang; Hu, Ge; Dong, Hong (Frontiers in Cellular and Infection Microbiology, 2020)
Gut microbiota is critical as either the maker of risk or the contributor of therapy on bacterial infection. Both traditional Chinese medicine compound, Pulsatilla Decoction (PD) and the antibiotic, Levofloxacin Hydrochloride (LVX) have the antibacterial activity. However, how the changes of gut microbiota after PD or LVX treatment is hitherto not explicated. Herein, we aim to compare gut microbiota after PD or LVX treatment on Escherichia coli induced infection. Results showed that PD exhibited a valid therapeutic approach for E. coli infection, which also showed an intestinal protection and had less IL-8 and ICAM-1 release. LVX treatment promoted the infection and ravaged gut microbiota by significantly decreasing Bacteroidetes and increasing Firmicutes. In turn, PD regulates the balance of gut microbiota via restoring the composition of the gut microbiota in Bacteroietes spp. Our work will highlight the mechanism of Chinese herbal formula and extend the usage of PD as veterinary medicine, feed medicine additive, pre-mixing agent to improve the production of animal derived foods.